MENGEMBANGKAN PERILAKU ASERTIF KEPALA SEKOLAH - Nurtanio Agus Purwanto (Jurnal Internasional Manajemen Pendidikan, 2010)
Leadership in education plays a key role in management. Therefore, through leadership, management functions can be run in accordance with an agreed mechanism for achieving educational goals. Leadership is a core part in management. As an art to influence others, whether the leadership is strong or weak authority provides a direct consequence in the institute management’s success or fail. No exception the educational institutions. Educational leaders require assertive behavior that is the behavior that include an expression or declaration of interests, needs, opinions, thoughts, and feelings, which are done wisely, fairly, and effectively, so that our rights can be maintained with due regard to respect for equality and rights with other people. Through such assertive behavior, the educational leaders can manage the whole personality, and it will impact on the sustainability development of education organization. Assertive behavior is developed as an effort to make the leader a model or example through self-discipline and cooperation.   Keywords: Assertive behavior, educational leaders.